2020
DOI: 10.1088/1361-6528/abcd62
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-assisted plasmonic enhancement for DNA detection on a graphene-based portable surface plasmon resonance sensor

Abstract: The impact of different gold nanoparticles (GNPs) structures on the plasmonic enhancement for DNA detection is investigated on a few-layer graphene (FLG) surface plasmon resonance (SPR) sensor. Two distinct structures of gold nanourchins (GNu) and gold nanorods (GNr) were used to bind the uniquely designed single-stranded probe DNA (ssDNA) of Mycobacterium tuberculosis complex (MTBC) DNA. The two types of GNPs-ssDNA mixture were adsorbed onto the FLGcoated SPR sensor through the π-π stacking force between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…In another approach, Prabowo et al (2021) reported a graphene-based portable surface plasmon resonance (SPR) sensor for the detection of MTC DNA [ 79 ]. In this approach, a graphene layer was deposited on an Au-SPR chip by drop-casting.…”
Section: Sensors For Commonly Reported Pathogenic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In another approach, Prabowo et al (2021) reported a graphene-based portable surface plasmon resonance (SPR) sensor for the detection of MTC DNA [ 79 ]. In this approach, a graphene layer was deposited on an Au-SPR chip by drop-casting.…”
Section: Sensors For Commonly Reported Pathogenic Bacteriamentioning
confidence: 99%
“…In contrast, the estimated signal of GNr reached only 8.2 pmol/L of cssDNA. Overall, this optical biosensor offered a simple, time-saving, and cost-effective design for the detection of MTC, while providing a low LOD and high specificity in DNA sensing, which is very promising for early screening of bacterial infections [ 79 ].…”
Section: Sensors For Commonly Reported Pathogenic Bacteriamentioning
confidence: 99%
“…The plasmonic-based platforms are well known for the high sensitivity performance of biosensors [29,38].…”
Section: Plasmonic-based Biosensorsmentioning
confidence: 99%
“…Other attempts are by downscaling the sensing area into two-dimensional (2D) or onedimensional (1D) structures [60][61][62][63]. The 2D materials for the advanced sensing structure can be graphene [38,64,65] that enhances the detection down to attomolar to femtomolar ranges [66][67][68]. Other 2D materials, such as molybdenum disulfide (MoS2) reported being able to boost the detection down to the femtomolar range for protein [69] dan DNA detection [70], respectively.…”
Section: Sensitivitymentioning
confidence: 99%
“…More recently, a new coronavirus detection chip based on nano-plasma optical sensing technology has been proposed by Huang and others (Huang et al, 2021), which has made a significant contribution to epidemic prevention and control. Additionally, the surface plasmon resonance technology has made major breakthroughs in biological imaging (Shpacovitch et al, 2015), DNA separation (Liu and Huang, 2013) and detection of small molecules (Prabowo et al, 2020). It also makes contributions to the production of hyperthermia reagents for cancer (Rozanova and Zhang, 2009) and research in the field of molecular biology.…”
Section: Introductionmentioning
confidence: 99%